Prevalence and Molecular Characterization of Campylobacter spp. Isolated from Patients with Diarrhea in Shunyi, Beijing - Li, Ying; Zhang, Shuang; He, Mu; Zhang, Yanchun; Fu, Yanyan; Liang, Hao; Jing, Hongbo; Li, Yindong; Ma, Hongmei; Zhang, Maojun (Frontiers in Microbiology, 2018)
Bacterial pathogens have been confirmed as the major cause of acute diarrhea among outpatients in China. In this study, 370 stool samples from the patients aged from 15 to 87 years old with diarrhea were collected over 12 months (from May 2016 to April 2017) in two hospitals in Shunyi, Beijing. Bacterial isolation was performed for the common enteric pathogens: Campylobacter, Salmonella, Shigella, Diarrheagenic E. coli, and Vibrio parahaemolyticus for 370 samples. The filtration method was used for the Campylobacter isolation in this study. The prevalence and molecular characterization of the Campylobacter were investigated. The isolation ratio for Campylobacter, Salmonella, Shigella, Diarrheagenic E. coli, and Vibrio parahaemolyticus was 7.0% (26/370), 6.2% (23/370), 0.3% (1/370), 7.3% (27/370), and 10.3% (38/370), respectively. Based on the isolation result, Campylobacter positive cases presented in almost every month of the whole year and the isolation ratio was the highest among the tested pathogens during October to March. There was no significant difference between genders of Campylobacter positive cases. More Campylobacter positive cases presented dehydration compared with those who were positive for Salmonella. Twenty-six Campylobacter isolates were obtained in this study and 24 of these were C. jejuni. The antibiotic susceptibility tests indicated that 83.3% (20/24) of the isolates exhibited resistance to three or more types of antibiotic. Twenty STs were identified for the 26 Campylobacter isolates and four novel STs were identified in this study. No clonal cluster was found among these isolates. This is the first study for Campylobacter isolated using the filtration method in China which indicated the Campylobacter infection might be seriously under-ascertained in the diarrheal patients in China.